Cu-Cr-Mg alloy with both high strength and high electrical conductivity manufactured by powder metallurgy process. (June 2021) - Li, Yidi; Yang, Biaobiao; Zhang, Ping; Nie, Yan; Yuan, Xiaobo; Lei, Qian; Li, Yunping
Highlights: Properties of powder metallurgy Cu-0.28Cr-0.19 Mg alloy were investigated. Alloy exhibits both higher mechanical properties and electrical conductivity. Grain refinement strengthening is the main reason for the high strength of the alloy. Abstract: In this study, microstructures, mechanical properties, and electrical conductivities of powder metallurgy (PM) Cu-0.28Cr-0.19 Mg alloy after cold-rolling and aging were investigated in detail. PM Cu-Cr-Mg alloy exhibits a combination of both higher mechanical properties and superior electrical conductivity compared to the corresponding casting Cu-Cr-X alloys. Such excellent performances are closely related to the more uniform and finer microstructures generated in PM process. Strengthening from second phase precipitation, grain boundary, and dislocation in the present PM Cu-Cr-Mg alloy were calculated to be approximately 43.65, 24.50, and 23.12 % of yield strength, respectively. The grain boundary strengthening is the main reason for the higher strength of the present PM Cu-Cr-Mg alloy and is approximately 325 % higher than that of the corresponding casting Cu-Cr-Mg alloy. The gradually decreased activation energy of PM Cu-Cr-Mg alloy with increasing reduction rate suggests that deformation significantly accelerates the precipitation behavior during the subsequent aging process.